Effectiveness of Sample Pooling Strategies for SARS-CoV-2 Mass Screening by RT-PCR: A Scoping Review - Deka, Sangeeta; Kalita, Deepjyoti (Journal of Laboratory Physicians, 2020)
The ongoing COVID-19 pandemic has hugely impacted the economy of many countries, and there is an acute shortage of diagnostic resources. With the exponential increase in the number of cases and necessity to screen large number of people, there is a steep increase in the demand for diagnostic kits. Pooled-sample testing is a promising strategy to screen a large population rapidly with limited resources. The aim of this work was to compile a cohesive literature review of the effectiveness and accuracy of pooled-sample testing in the detection of SARS-CoV-2 and critically analyze its limitations. Medline, Google Scholar, Embase, and preprint servers (e.g., bioRxiv) were searched for literature on pooled testing for diagnosis of COVID-19, and out of initial 60 articles/reports, nine original articles were retained. Optimal pool size (number of samples in a pool) seemed to be dependent on factors like prevalence or rate of positivity in community. In low-prevalence localities pool size of around 30 seemed to be effective as observed by some authors. All the researchers had found significant reduction in number of tests (depending on pool size, stages, and pooling design), leading to conservation of resources. Pooling can be done with extracted RNA eluate or directly with patient’s sample before extraction. This leads to further reduction in consumables, time and manpower. Risk of false negativity in samples with high-threshold cycle (i.e., low-viral load) value was a concern. Some researchers suggest adding few additional cycles to lower the chances of missing positive cases with low-Ct value. Lower limit of detection (LoD) of RT-PCR kits, that is, sensitivity of kits was another factor to consider. Thus, in a country like India, given the economic benefit and scarcity of resources, pooling strategy can be very effective, especially in low-prevalence areas and in low-risk contacts.
Keywords: COVID-19; pooling; RT-PCR; SARS-CoV2; group test